Resurgence of Aflatoxicosis and the Role of Physical Exercise in Aflatoxin Metabolism in Laying Hens - Yabo , Y.A.; Raji, A.A.; Muftahu, L.O.; Abdullahi, J.; Jibril, A.H.; Hassan, I.M. (International Journal of Poultry Science, 2019)
Background and Objective: Aflatoxins are among the top common courses of aflatoxicosis in poultry. In addition to the huge economic implications of aflatoxicosis to the poultry industry, aflatoxins are life-threatening to birds when present above the standard tolerable limit in poultry feed. Despite several reports on the levels of aflatoxin present in tested feed samples, natural cases of aflatoxicosis in poultry are rarely reported. The present study was conducted to report a natural case of aflatoxicosis in two different poultry farms where laying hens were fed with an aflatoxin contaminated feed. Materials and Methods: We collected a sample of poultry feed suspected to be contaminated with aflatoxins for analysis. Direct competitive ELISA using AgraQuant® total aflatoxin (TA) test kit was used to quantify the total aflatoxin level in the collected feed sample. Results: Laboratory analysis of the feed sample showed a high level of total aflatoxin of up to 320 ppb (parts per billion). This is 15 times above the FAO action point (20 ppb) for total aflatoxin in finished poultry feed. A post-mortem examination of the affected birds revealed typical lesions associated with aflatoxicosis. Interestingly, hens raised in a deep litter system showed more resistance to the same level of aflatoxin exposure when compared to hens raised in the cage system. Conclusion: We conclude that there is a surge in the natural cases of aflatoxicosis in poultry due to high level of aflatoxins in poultry feed, especially in developing tropical countries like Nigeria. We postulate that physical exercise could affect the rate of aflatoxin metabolism in poultry.